2018
DOI: 10.1111/mec.14704
|View full text |Cite
|
Sign up to set email alerts
|

Temperature gradient affects differentiation of gene expression and SNP allele frequencies in the dominant Lake Baikal zooplankton species

Abstract: Local adaptation and phenotypic plasticity are main mechanisms of organisms' resilience in changing environments. Both are affected by gene flow and are expected to be weak in zooplankton populations inhabiting large continuous water bodies and strongly affected by currents. Lake Baikal, the deepest and one of the coldest lakes on Earth, experienced epilimnion temperature increase during the last 100 years, exposing Baikal's zooplankton to novel selective pressures. We obtained a partial transcriptome of Episc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 98 publications
2
11
0
Order By: Relevance
“…In this study, we found 349 candidate loci identified by at least two outlier tests. The outliers from Bayenv2, LFMM, and PCAdapt included 1.14, 4.31, and 7.81% of the total number of loci analyzed from our RNA-Seq dataset, respectively; these percentages are similar to the candidate coverage reported in other studies (2.52, 4.87, and 7.52%, respectively) using at least one of the same software programs [83, 84]. The overall percentage of outliers may be affected by species and the dataset.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, we found 349 candidate loci identified by at least two outlier tests. The outliers from Bayenv2, LFMM, and PCAdapt included 1.14, 4.31, and 7.81% of the total number of loci analyzed from our RNA-Seq dataset, respectively; these percentages are similar to the candidate coverage reported in other studies (2.52, 4.87, and 7.52%, respectively) using at least one of the same software programs [83, 84]. The overall percentage of outliers may be affected by species and the dataset.…”
Section: Discussionsupporting
confidence: 81%
“…In the porcelain crab Petrolisthes cinctipes , the homolog of twinstar ( cofilin) was upregulated in response to heat stress [72]. Overall, the actin cytoskeleton was shown to play a central role in the cold hardiness of various species, including animals (e.g., D. melanogaster [11,73], mosquitos [74], crickets [14,15], zooplankton [75], silkworm [76]) and plants (e.g., alfalfa [77], pear [78]). Our results in D. ananassae support the important role of actin polymerization in cold hardiness.…”
Section: Discussionmentioning
confidence: 99%
“…26 and Bowman et al . 27 can be extended to other stressors than temperature. Last, our database will also help interpreting the results of studies on adaptation in natural populations as well as ecological experiments.…”
Section: Resultsmentioning
confidence: 99%